The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2020
DOI: 10.24847/77i2020.245
|View full text |Cite
|
Sign up to set email alerts
|

“Like a Tree Without Leaves”: Syrian Refugee Women and the Shifting Meaning of Marriage

Abstract: There is a growing body of feminist scholarship that highlights aspects of agency and empowerment of the refugee woman, mostly through citing examples of women challenging patriarchy and cultural norms. Extending the latter, I use a decolonizing framework to examine how refugee women strive for autonomy and empowerment through acceptingthose norms and utilizingthem strategically. In doing so, I reveal a more complex relationship between agency and victimhood and how they relate to other notions such as empower… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 0 publications
0
4
2
Order By: Relevance
“…The fact that women may exercise agency to choose not to marry because marriage may hold the potential to undermine them, represents an important contribution of the study. This finding contrasts with existing literature in the region which links marriage to improved social status for women (Salamandra, 2006; Taha, 2020), instead suggesting that there are situations where women may decide marriage is not the best option. In these accounts, women's role in choosing (or not choosing) spouses also places them in positions of power, which is a less-visible narrative about Middle Eastern women both in academic literature as well as in humanitarian reports.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…The fact that women may exercise agency to choose not to marry because marriage may hold the potential to undermine them, represents an important contribution of the study. This finding contrasts with existing literature in the region which links marriage to improved social status for women (Salamandra, 2006; Taha, 2020), instead suggesting that there are situations where women may decide marriage is not the best option. In these accounts, women's role in choosing (or not choosing) spouses also places them in positions of power, which is a less-visible narrative about Middle Eastern women both in academic literature as well as in humanitarian reports.…”
Section: Discussioncontrasting
confidence: 99%
“…By exercising agency in deciding not to marry, the example of Khadija illustrates how marriage may not always be the solution to strengthening a woman's position but may at times undermine it. This contrasts with other literature that emphasizes the importance of marriage for social position (Salamandra, 2006; Taha, 2020).…”
Section: Resultscontrasting
confidence: 75%
“…Melissa, for example, reported that she had seen a number of such cases at her centre. While recent research has suggested that refugee women's decisions to marry are agentic and empowering acts (Taha, 2020), there is also a body of research which documents how early marriage, as a coping mechanism, can result in abuse and the limiting of freedoms such as attending school (e.g. DeJong et al, 2017;Hattar-Pollara, 2019;UNHCR, 2016).…”
Section: Educational Constraints For Young Refugee Womenmentioning
confidence: 99%
“…Although matriarchal families exist across different conditions and settings, we suggest that the subordinate integration of these elder women in Canada mediates their former power as matriarchs. This heeds the call by feminist scholars to add to the "upsurge" in work on Arab women's public rights, identities, and political participation by also studying dynamic changes in family life (Johnson, 2018, p. 467;Taha, 2020) as well as to contribute to emerging knowledge in migration studies about Syrian resettlement in Canada (Hamilton et al, 2020;Hynie, 2018;Oudshoorn et al, 2020).…”
Section: Goals and Objectivesmentioning
confidence: 99%
“…It follows, then, that an emerging body of research with SRRI newcomers attends to their integration-related experiences and outcomes (consult, for example, Hamilton et al, 2020, Kyriakides et al, 2018, Taha, 2020. We know less, however, about the experiences of older adults in this migration wave (Boutmira, 2021).…”
Section: Syrian Resettlement In Canada (2015-present)mentioning
confidence: 99%